Correlation between electromechanical parameters (NOGA XP) and changes of myocardial ischemia in patients with refractory angina - Kurzelowski, Radosław; Barański, Kamil; Caluori, Guido; Szot, Wojciech; Grabowski, Krzysztof; Michalewska-Włudarczyk, Aleksandra; Syzdół, Marcin; Kuczmik, Wacław; Błach, Anna; Ochała, Beata; Hudziak, Damian; Wilczek, Jacek; et al. (Postepy w kardiologii interwencyjnej, 2021)
INTRODUCTION: Cell therapy has the potential to improve symptoms and clinical outcomes in refractory angina (RFA). Further analyses are needed to evaluate factors influencing its therapeutic effectiveness. AIM: Assessment of electromechanical (EM) parameters of the left ventricle (LV) and investigation of correlation between EM parameters of the myocardium and response to CD133+ cell therapy. MATERIAL AND METHODS: Thirty patients with RFA (16 active and 14 placebo individuals) enrolled in the REGENT-VSEL trial underwent EM evaluation of the LV with intracardiac mapping system. The following parameters were analyzed: unipolar voltage (UV), bipolar voltage (BV), local linear shortening (LLS). Myocardial ischemia was evaluated with single-photon emission computed tomography (SPECT). The median value of each EM parameter was used for intra-group comparisons. RESULTS: Global EM parameters (UV, BV, LLS) of LV in active and placebo groups were 11.28 mV, 3.58 mV, 11.12%, respectively; 13.00 mV, 3.81 mV, 11.32%, respectively. EM characteristics analyzed at global and segmental levels did not predict response to CD133+ cell therapy in patients with RFA (Global UV, BV and LLS at rest R = -0.06; R = 0.2; R = -0.1 and at stress: R = 0.07, R = 0.09, R = -0.1, respectively; Segmental UV, BV, LLS at rest R = -0.2, R = 0.03, R = -0.4 and at stress R = 0.02, R = 0.2, R = -0.2, respectively). Multiple linear regression of the treated segments showed that only pre-injection SPECT levels were significantly correlated with post-injection SPECT, either at rest or stress (p < 0.05). CONCLUSIONS: Electromechanical characteristics of the left ventricle do not predict changes of myocardial perfusion by SPECT after cell therapy. Baseline SPECT results are only predictors of changes of myocardial ischemia observed at 4-month follow-up.
Keywords: cell therapy; electromechanical mapping; refractory angina; NOGA XP; CD133+